Photographing Fireworks : the Right Gear, Location, and Techniques for Capturing Beautiful Images - Hess, Alan (Peachpit Press, 2013)
In Photographing Fireworks, author and photographer Alan Hess teaches you how to capture stunning photos of fireworks displays, offering helpful tips to guide you in the field. Alan covers the equipment setup that you'll need to snap the perfect shot, as well as the fundamentals of exposure and composition. He shares the trick to getting just the right amount of exposure – a key factor in shooting the light trails of fireworks against the night sky – walking you through using the manual exposure and bulb settings on your camera. Finally, he discusses practical considerations for shooting such an ephemeral and challenging subject in crowds and at night, and how to get the best shots you can during the finale of a show. Follow along with Alan Hess and you will: Learn to use your camera's settings to get the perfect exposure to capture fireworks and other light trails Get tips to ensure that you find the best location, orientation, and aperture adjustment for your images Gain practical on-the-ground strategies for before, during, and at the end of the show.